Student work and nursing student's performance during study - Sedina Kalender Smajlović; Saša Kadivec; Brigita Skela-Savič (Nurses and Midwives Association of Slovenia, 2014)
Introduction: According to different studies, student work has both positive and negative effects on the academic performance of nursing students. The purpose of the study was to examine the effect of student work based on a sample of Slovenian nursing students. Methods: The method of non-experimental quantitative research with a sampling survey was used. 432 nursing students participated. The reliability of the questionnaire was determined by internal consistency analysis (from 0.608 to 0.753) and factor analysis. The data were collected in October and November 2012. Descriptive statistics, the chi-square test, correlation analysis and ANOVA were used for the statistical analysis. Results: Students of four higher education institutions did not provide statistically significant differences in the assessment of their financial status (p = 0.189). The number of hours of student work does not statistically correlate (p = 0.776) with the time for studying. The monthly total of the hours of student work revealed a statistically significant difference (p = 0.001), with students at higher education institution A stating the least hours of student work (x = 19.9), and students at higher education institution B stating the greatest amount of student work (x = 48.5). Discussion and conclusion: The monthly amount of hours of student work does not affect students' academic performance. Students opt for student work because they wish to acquire clinical experience, clinical practice, meet potential employers and improve their employment prospects after graduation.